In the context of constant coefficient linear matrices, why is it okay to add one row to another? I understand multiplying an equation by a constant, and even adding a number to both sides of an equation. But, how does adding one equation to another not change it? I have used this plenty of times in my study, but it only just occurred to me that this isn't the same as, say,

$ q = 2 \cdot x$


$q + 5 = 2 \cdot x + 5 $

So how does it work, that adding/subtracting two equations together doesn't change the solution of

$ Ax = b$

  • 2
    $\begingroup$ It's basically a consequence of $a=b\ \&\ c=d\implies a+c=b+d$. $\endgroup$ – Akiva Weinberger Feb 1 '16 at 0:27
  • 1
    $\begingroup$ @AkivaWeinberger: no, it's a consequence of $a = b \mathrel{\&} c = d \iff a = b \mathrel{\&} a + c = b + d$ $\endgroup$ – Rob Arthan Feb 1 '16 at 0:32
  • $\begingroup$ @RobArthan Yes, that implies it more directly. :) $\endgroup$ – Akiva Weinberger Feb 1 '16 at 0:33
  • $\begingroup$ @AkivaWeinberger: cheers! it's a game of two halves $\ddot{\smile}$! $\endgroup$ – Rob Arthan Feb 1 '16 at 0:35
  • $\begingroup$ Thank you for asking the question: it's really good that you aren't just swallowing mathematics without thinking about it! A lot of my students wouldn't be able to tell me why adding equations is OK! $\endgroup$ – Frentos Feb 5 '16 at 12:42

Suppose we have two equations $\left\{\begin{array}{rrrcl}2x&+3y&-z&=&4\\x&-2y&+2z&=&6\end{array}\right.$

We can add $6$ to both sides of the top equation in the usual way like this: $$2x + 3y - z + 6 = 4 + 6$$ but because of the 2nd equation, $6$ is the same as $x-2y+2z$, so we can write: $$2x + 3y - z + (x-2y+2z) = 4 + 6$$

That (hopefully!) convinces us that adding equations is OK.

But why doesn't this change the solution space? It may help to think about the true/false value of the equations for different $(x,y,z)$.

  • A solution makes both equations true; a non-solution makes at least one of the equations false.

  • If we consider a solution, both equations are true for those values; if both equations are true, the sum of the equations is true (read over the example above thinking about truth/falsehood), so no solutions are lost.

If we consider a non-solution, the situation is a bit trickier. We might start with $$\begin{array}{rcl}y&=&2x\\y&=&4x\\\hline 2y&=&6x\end{array}$$ The non-solution $x=1,y=3$ makes both the first two equations false, but makes the last equation true! How do we know non-solutions can't sneak in this way? I can't think of a succinct explanation of why this is not a problem in general, but:

  • If you shift your point of view to logic, it's not a problem that false premises can lead to any conclusion, including true conclusions)
  • In the context of matrices or systems of equations it's not a problem because you'll always have some equation hanging around that the non-solution makes false. In a way, you can view reducing an augmented matrix to row echelon form and getting an inconsistency as pushing the falsehood of any candidate solution into one equation like $0x+0y+0z=5$. Consider a reduced matrix with one solution: $\left|\begin{array}{ccc|c}1&0&0&2\\0&1&0&3\\0&0&1&-4\end{array}\right|$. The last equation in the matrix, $z=-4$, is true for a non-solution like $x=0,y=1,z=-4$, but it's ruled out when you consider the other equations.
  • $\begingroup$ This is perfect. Thank you for a very informative answer. $\endgroup$ – justthom8 Feb 5 '16 at 19:47

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.